BodyCity: The Body of the visually impaired person in the City and its implications as Blind Flâneur (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The present work seeks to reflect on the Body of the visually impaired person in the City, seeking to understand its artistic and political implications in urban space. Due to this bias, the text presents a reflection from the research Blind City: a somatic-performative urban with visually impaired actors/performers in the city, carried out throughout the doctorate, at the Federal University of Bahia, between 2014 and 2018 (Ferreira da Silva, 2018). Thus, the article describes about the urban intervention of two visually impaired artists, being Gilson Coelho and Valmira Noia. In addition to bringing to the discussion the term Blind Flâneur, as a result of the experience and experience of the Body of the visually impaired person as a flâneur in the City.
Keywords: CorpoCity; Blind Flâneur; Urban Intervention; Visually impaired person